2022
DOI: 10.3390/jcm11102689
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Outcome of Head and Neck Cancer of Unknown Primary (HNCUP)

Abstract: Background: This study on patients with head and neck cancer of unknown primary (HNCUP) assesses the impact of surgical and non-surgical treatment modalities and the tumour biology on the oncological outcome. Methods: A total of 80 patients with HNCUP (UICC I–IV) were treated with simultaneous neck dissection followed by adjuvant therapy, between 1 January 2007 and 31 March 2020. As the primary objective, the influence of treatment modalities on the overall survival (OS), the disease-specific survival (DSS) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 41 publications
0
10
0
2
Order By: Relevance
“…Squamous cell carcinoma (SCC) is the most frequently incriminated in the histopathology of head and neck CUP, its frequency being between 53% and 77% 9,10 . Of these, approximately 58% represent the common form of SCC, 15% being represented by adenocarcinomas, undifferentiated carcinomas, seromucous, basaloid or papillary carcinomas 10,11 .…”
Section: Squamous Cell Carcinomamentioning
confidence: 99%
See 2 more Smart Citations
“…Squamous cell carcinoma (SCC) is the most frequently incriminated in the histopathology of head and neck CUP, its frequency being between 53% and 77% 9,10 . Of these, approximately 58% represent the common form of SCC, 15% being represented by adenocarcinomas, undifferentiated carcinomas, seromucous, basaloid or papillary carcinomas 10,11 .…”
Section: Squamous Cell Carcinomamentioning
confidence: 99%
“…Also, the choice of radiotherapy as the only therapy in cN2, N3 cases seems to be associated with a poor prognosis in terms of survival compared to multimodal chemotherapy treatment or associated with surgery 9,48 .…”
Section: Prognosis Of Head and Neck Cancers Of Uknown Primarymentioning
confidence: 99%
See 1 more Smart Citation
“…Prognostic implications of HPV in the context of HNCUP are, perhaps, the point that brings up the most controversy within studies. Some authors did not find any difference in the prognosis of patients regarding HPV status [ 8 , 10 , 17 , 19 ], while some did, and even more so, suggested the possibility of de-intensification of treatment for this patient group [ 9 , 14 , 16 , 25 ]. Axelsson et al, specifically, reported that curatively treated HNCUP has a good survival, with an overall five-year survival rate of 82%, and found that p16 positivity is associated with significantly longer survival and a lower risk of tumor recurrence [ 8 ].…”
Section: Reviewmentioning
confidence: 99%
“…Other studies highlight that the N stage is a significant prognostic factor for overall survival in patients with HNCUP treated with curative intent [ 9 ]. In another study, the main poor prognostic factor was the development of distant metastases [ 10 ].…”
Section: Reviewmentioning
confidence: 99%